Kedalaman Materi Pembelajaran IPA di Sekolah dan Penguasaan Konsep Siswa - Rahayu Laelandi; Ari Widodo; Siti Sriyati (Jurnal Penelitian Pendidikan IPA, 2022)
The depth of science material in schools is related to the teacher's ability to master science concepts. A good teacher is a teacher who is able to compile the concept of science material in a planned manner. Such planning is for example compiling material in-depth or broadly, so that later students are able to master the concept optimally. This article aims to analyze the depth of science learning materials and students' conceptual mastery of the material presented by the teacher. Data were obtained by observing the delivery of concepts and duration used by the teacher and students' mastery of concepts from questions in the form of a description of 6 questions. The sample used is a science teacher and 22 students. The results showed that the teacher conveyed the material not in-depth because there were several concepts with incomplete or separate sub-concepts. As a result, students' mastery of concepts is low even though in question number 3 about the concept of the lithosphere, most of the students on average answered correctly and correctly when compared to the answers to other questions. The high mastery of students' concepts is because the sub-concepts conveyed by the teacher are only mentioned and are not explained in-depth, while the low mastery of students' concepts is because there are too many supporting sub-concepts and the concepts are too deep, thus requiring students' critical thinking skills.